Theoretical and comparative perspectives on nationalism : new directions in cross-cultural and post-communist studies - Kuzio, Taras (Soviet and post-Soviet politics and society, 2007)
This volume brings together 15 articles divided into four sections on the role of nationalism in transitions to democracy, the application of theory to country case studies, and the role played by history and myths in the forging of national identities and nationalisms. The book develops new theories and frameworks through engaging with leading scholars of nationalism: Hans Kohn's propositions are discussed in relation to the applicability of the term 'civic' (with no ethno-cultural connotations) to liberal democracies, Rogers Brubaker over the usefulness of dividing European states into 'civi.